System Integration for Medical Data Dissemination and Multimedia Communication in the Implementation of Tele-ECG and Teleconsultation - Anak Agung Ngurah Ananda Kusuma; Tahar Agastani; Christian Wisnu Purnaadi; Triawan Nugroho (Buletin Pos dan Telekomunikasi, 2020)
One of the options to extend medical services coverage is deploying a telemedicine system, where medical personnel make use of ICT (Information and Communication Technology) to overcome distance and time constraints. The implementation of telemedicine systems in Indonesia faces challenges posed by the lack of ICT infrastructure availability, such as communication networks, data centres, and other computing resources. To deal with these challenges, a telemedicine innovation needs to produce a modular and flexible system that is adaptive to medical services needed and the available ICT infrastructure. This paper presents research and development of a telemedicine system prototype for tele-electrocardiography (tele-ECG) and teleconsultation. The contributions offered are integrating system from various open-source modules and the system operational feasibility based on its function and performance. The research is conducted on a testbed which represents various components involved in the telemedicine system operation. Experiments are carried out to assess the system functionality and observe whether tele-ECG and teleconsultation reach their expected performance. Experiment results show that the system works properly and recommend several multimedia communication modes to achieve the target quality based on the available network bandwidth.